1995
DOI: 10.1002/bit.260460615
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and in vitro analysis of microencapsulated genetically engineered E. coli DH5 cells for urea and ammonia removal

Abstract: This article describes a novel method of urea and ammonia removal using microencapsulated, genetically engineered Escherichia coli DH5 cells. Optimization of bacterial cell encapsulation was carried out. The optimal method consists of alginate 2.00% (w/v) at a flow rate of 0.0724 mL/min and a coaxial air flow rate of 2.00 L/min. This produces spherical, alginate-poly-L-lysine-alginate (APA) microcapsules of an average 500 +/- 45 mum diameter. Increasing the concentration of alginate from 1.00% to 1.75% improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…Our in vitro results [25] show that 40.00 B 8.60 g of encapsulated E. coli DH5 can remove 40 g of urea (100 mg/dl in 40 liters). There was no increase in the ammonia level.…”
Section: In Vitro Removal Of Urea Ammonium Electrolytes and Other Mmentioning
confidence: 86%
See 1 more Smart Citation
“…Our in vitro results [25] show that 40.00 B 8.60 g of encapsulated E. coli DH5 can remove 40 g of urea (100 mg/dl in 40 liters). There was no increase in the ammonia level.…”
Section: In Vitro Removal Of Urea Ammonium Electrolytes and Other Mmentioning
confidence: 86%
“…Prakash and Chang [23][24][25] therefore studied the oral use of microencapsulated genetically engineered nonpathogenic Escherichia coli DH5 cells containing Klebsiella aerogenes urease gene in rats with renal failure.…”
Section: Do Orally Administered Artificial Cells Containing Geneticalmentioning
confidence: 99%
“…The alginate-poly-l-lysine (PLL) system used here utilizes the natural polymer alginate, but the challenge in producing such uniform capsules is to ensure excellent repeatability and reproducibility both within and between batches. The technique used to produce alginate-PLLalginate (APA) capsules is based on the entrapment of individual cells or tissue in an alginate droplet that is then transformed into a rigid bead by gelation in a Ca 2+ -rich solution [17,26].…”
Section: Artificial Cell Preparation Technologymentioning
confidence: 99%
“…Thus, micro encapsulation of cells is currently being studied extensively to confront the limitations of traditional immobilization technologies. Artificial cell microencapsulation is used to encapsulate biologically active materials in specialized ultra-thin semipermeable polymer membranes [4,17]. The principle of mammalian cell microencapsulation is that the permeability of the membrane is engineered to allow the passage of oxygen, important nutrients and cellular products, but stops the ingress of immunoglobulins or immune cells responsible for transplant rejection [18].…”
Section: Introduction To Artificial Cellsmentioning
confidence: 99%
“…The conventional APA microcapsule has thus been shown to pose limitations for general use in the oral administration of microencapsulated bacterial cells for therapy. Some studies have shown that this classic formulation has inadequate stability in the GI tract for some applications [106], while other researchers have shown that APA microcapsules have a controversial permeability [107]. Furthermore, it has been reported that it is difficult to obtain a membrane, optimizing all the properties requested for a successful clinical application, by the process of binary polyelectrolyte complexation [108].…”
Section: Potential Of Artificial Cells For Oral Delivery Of Live Bactmentioning
confidence: 99%